2016
DOI: 10.1038/ncomms13595
|View full text |Cite
|
Sign up to set email alerts
|

Repression of RNA polymerase by the archaeo-viral regulator ORF145/RIP

Abstract: Little is known about how archaeal viruses perturb the transcription machinery of their hosts. Here we provide the first example of an archaeo-viral transcription factor that directly targets the host RNA polymerase (RNAP) and efficiently represses its activity. ORF145 from the temperate Acidianus two-tailed virus (ATV) forms a high-affinity complex with RNAP by binding inside the DNA-binding channel where it locks the flexible RNAP clamp in one position. This counteracts the formation of transcription pre-ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(61 citation statements)
references
References 67 publications
4
57
0
Order By: Relevance
“…Encounters between the Acidianus two-tailed virus (ATV) and S. solfataricus are witnessed by the presence of several ATV genome-derived CRISPR spacers in the hosts' CRISPR arrays, including sequences mapping to a small gene called ORF145 [101]. ORF145, also called RIP (RNAP inhibitory protein), binds tightly to the inside of the DNA-binding channel of the host RNAP, thereby locking the RNAP clamp into a fixed position [102]. This counteracts the formation of transcription initiation complexes and inhibits abortive and productive transcription ( Figure 6).…”
Section: Global Inhibition Of Transcription In the Host-virus Arms Racementioning
confidence: 99%
See 1 more Smart Citation
“…Encounters between the Acidianus two-tailed virus (ATV) and S. solfataricus are witnessed by the presence of several ATV genome-derived CRISPR spacers in the hosts' CRISPR arrays, including sequences mapping to a small gene called ORF145 [101]. ORF145, also called RIP (RNAP inhibitory protein), binds tightly to the inside of the DNA-binding channel of the host RNAP, thereby locking the RNAP clamp into a fixed position [102]. This counteracts the formation of transcription initiation complexes and inhibits abortive and productive transcription ( Figure 6).…”
Section: Global Inhibition Of Transcription In the Host-virus Arms Racementioning
confidence: 99%
“…Because RIP, like TFS4, binds directly to RNAP, both host and virus promoters are inhibited in a global fashion. While the regulatory rationale behind this mechanism is still unclear, it is likely that the inhibition of transcription attenuates or even prevents the activation of the type IIIb CRISPR-Cas system and expression of anti-ATV CRISPR RNAs, while still enabling transcription on viral genes required for virus proliferation [102].…”
Section: Global Inhibition Of Transcription In the Host-virus Arms Racementioning
confidence: 99%
“…The inability of TFS DE-AA to properly donate acidic residues to the active site of RNAP abrogates its function as a cleavage stimulatory factor. Backtracking can result from extended pausing (Nudler, 2012;Imashimizu et al, 2013;Weixlbaumer et al, 2013;Hein et al, 2014;Imashimizu et al, 2015;James et al, 2017;Lerner et al, 2016;Gabizon et al, 2018), and the configuration of mobile-domains of RNAP is known to modulate the propensity to pause and the duration of pausing Martinez-Rucobo et al, 2011;Chakraborty et al, 2012;Weixlbaumer et al, 2013;Hein et al, 2014;Jun et al, 2014;Schulz et al, 2016;Sheppard et al, 2016;Bernecky et al, 2017;Feklistov et al, 2017;Kang et al, 2017;Duchi et al, 2018). We thus examined whether addition of Spt4 and/or Spt5 would influence the efficiency of RNA cleavage, with transcript cleavage also serving as a proxy for the propensity to, and depth of backtracking.…”
Section: Transcription Factor S (Tfs) But Not Spt4-spt5 Stimulates mentioning
confidence: 99%
“…Indeed, Rpo8 and -13 are prominent in distinguishing MSDDRPs from different archaeal species and phyla (79). Recent studies have shown how virology and RNA polymerase structural biology in the archaea have the capacity to cross-inform (82).…”
Section: Archaeal Msddrpsmentioning
confidence: 99%